PENGARUH KOMPETENSI DAN BEBAN KERJA SDM TERHADAP KUALITAS HASIL AUDIT DANA DESA DI INSPEKTORAT KABUPATEN LAMPUNG UTAR - Ardansyah - Ardansyah (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
This study aims to examine the effect of the competence and workload of human resources partially and simultaneously on the quality of the audit results of village funds at the Inspectorate of North Lampung Regency. The respondents of this study were 75 of 76 employees at the Inspectorate of North Lampung Regency. The data collection method used in this study was carried out with the main/principal method and supporting methods. The main method uses a questionnaire, while the supporting method uses interviews and documentation. The research approach used in this study is a quantitative approach using validity and reliability tests, classical assumption tests, multiple linear regression analysis and determination using IBM SPSS Statistics Version 26 software analysis tools. The results show that the independent variable is competence (X1). significant effect on the variable depending on the quality of audit results, workload (X2) has no significant effect on the audit quality variable, and competence and workload simultaneously have a significant effect on the quality of audit results.